PERBEDAAN IMPLEMENTASI TIPE DISCOVERY LEARNING TERHADAP KEMAMPUAN KOGNITIF, KETERAMPILAN FREE DISCOVERY, DAN PENGEMBANGAN KARAKTER KEMANDIRIAN SISWA SMP - Karumikawati, Tunjung Paryana; Yuanita, Leny; Susantini, Endang (JPPS (Jurnal Penelitian Pendidikan Sains), 2012)
The objective of this research is to compare the effectiveness of the guided discovery and the less structured discovery methods cognitive ability, free discovery skill, and autonomous character of the Junior High School. Forty Ponorogo Junior High School students have divided into two research classes were involved in this investigation using The Method of Science as the subject matter. The research was implemented in two phase, the development of the discovery learning resources, using the Kemp model, and the implementation of learning resources using the matching only pretest-posttest control group design (quasi experiment). From the hypothesis test (?: 0,005) showed that: (1)Cognitive skill of less structured discovery class higher than guided discovery class (Sig. 0.0025<?). The individual cognitive skill of guided discovery students increased from 20% to 65%, and for less structured discovery students increased from 10% to 80%; (2)Free discovery skill and autonomous character of less structured discovery class not higher than guided discovery class (free discovery skill Sig. 0,467>?; autonomous Sig.; 0,031; 0,028>?)  . Free discovery skill of guided discovery students increased from 20% to 80%, and that of less structured discovery students increased from 10% to 35%. The average percentage of autonomous character of guided discovery students ranges from 64,29% to 90,48%, and that of less structured discovery students ranges from 71,43% to 90,48%. The shortage of time allocation for the teaching and learning process was the main obstacle. Penelitian ini bertujuan untuk membandingkan tipe pembelajaran discovery (guided discovery dan less structured discovery) terhadap kemampuan kognitif, keterampilan free discovery, dan kemandirian siswa SMP. Subjek penelitian sejumlah 40 siswa yang dibagi dalam 2 kelas penelitian di SMP Negeri 1 Ponorogo kelas VII dengan materi pembelajaran metode ilmiah. Penelitian dilaksanakan dalam dua tahap, yakni tahap pengembangan perangkat pembelajaran discovery mengikuti rancangan Kemp dan tahap penerapan perangkat pembelajaran menggunakan rancangan penelitian the matching only pretest-posttest control group design (quasi experiment). Hasil uji hipotesis (?: 0,005) menunjukkan bahwa: 1) Kemampuan kognitif kelas less structured discovery lebih tinggi dari kelas guided discovery (Sig. 0,0025<?). Pada kelas guided discovery, kemampuan kognitif berdasarkan ketuntasan individu mengalami peningkatan dari 20% menjadi 65% dan pada kelas less structured discovery mengalami peningkatan dari 10% menjadi 80%. 2) Keterampilan free discovery dan kemandirian siswa kelas less structured discovery tidak lebih tinggi dari kelas guided discovery (keterampilan free discovery Sig. 0,467> ?; kemandirian Sig. 0,031; 0,028>?). Pada kelas guided discovery, keterampilan free discovery mengalami peningkatan dari 20% menjadi 80% dan pada kelas less structured discovery mengalami peningkatan dari 10% menjadi 35%. Rata-rata persentase kemandirian pada kelas guided discovery bervariasi 64,29%  hingga 90,48% dan kelas less structured discovery antara 71,43%  hingga 90,48%. Waktu menjadi hambatan utama dalam penelitian ini sehingga dibutuhkan pengalokasian yang lebih baik pada setiap tahapan pembelajaran.